On beauty: an Islamic perspective - El-Nagar, Hassan Abdelrazig (s.n, 2012)
This research undertakes the task of defining, discussion and critically examining the different manifestations of the concept of beauty in Islam. It starts off by identifying the real meaning of beauty in Lisan al-Arab, the famous Arabic lexicon and then attempts to explain the authentic tradition reported in Muslim in which Abdullah ibn Mas'ud relates that "Allah is Elegant and Beautiful and He like elegance and beauty". Here he researcher totally relies on the explanations of the two most noted Muslims in the area of metaphysics, namely Imam al-Ghazali and Ibn Qayyim al-Jawziyya.